IMPLEMENTASI PENGELOLAAN HIBAH PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH PROVINSI SULAWESI TENGAH - Ahmad, Tamrin (Katalogis, 2015)
The research aimed to determine the implementation of grant management conducted by the regional finance and asset management in Central Sulawesi province and the factors that influenced the implementation of the grant management carried out either support or inhibit, the informants in this study was 5 forms that consist of 3 employees of the financial and asset management in Central Sulawesi province and 2 grantees.  Informant’s determination was done by purposive sampling. Data collection using observation, interviews and documentation. Data were analyzed by descriptive qualitative. The results showed that the implementation of grant management included communication, resources, disposition / attitude and bureaucratic structure have not been effective. Implementation of these policies were also influenced by various factors both support consisted of financial management policies and the number of personnel resources and hampering consisting of regional conditions and the quality of personnel resources. Researcher also suggested that increasing the effectiveness of policy implementation grants to improve the ability and knowledge and professionalism of personnel resources owned in understanding and implementing government policies, especially policies for the management of grants, provided technical guidance related to the grant management  personnel resources in order to improve the competence and professionalism therefore, could execute all programs and government policies, especially related to grants and policy operational  standards and procedures (SOP) on the management of grant thereafter shall be a decision and can be used as the gold standard in managing grants.